ĐKXĐ : \(x\ge-\dfrac{3}{8}\)
Ta có : \(\sqrt{8x+3}=9x^2+10x+\dfrac{9}{4}\)
\(\Leftrightarrow36x^2+40x+9-4\sqrt{8x+3}=0\)
\(\Leftrightarrow\left(36x^2+48x+16\right)-8x-3-4\sqrt{8x+3}-4=0\)
\(\Leftrightarrow\left(6x+4\right)^2-\left(\sqrt{8x+3}+2\right)^2=0\)
\(\Leftrightarrow\left(6x+\sqrt{8x+3}+6\right).\left(6x+2-\sqrt{8x+3}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\sqrt{8x+3}=-6x-6\left(1\right)\\\sqrt{8x+3}=-6x-2\left(2\right)\end{matrix}\right.\)
Giải (1) ta có :
(1) <=> \(8x+3=\left(-6x-6\right)^2\) (với \(-6x-6\ge0\Leftrightarrow x\le-1\))
\(\Leftrightarrow36x^2+64x+33=0\)
\(\Leftrightarrow\left(6x+\dfrac{16}{3}\right)^2+\dfrac{41}{9}=0\)
\(\Leftrightarrow x\in\varnothing\) => (1) vô nghiệm
Giải (2) ta có
(2) <=> \(8x+3=\left(-6x-2\right)^2\) (với \(x\le-\dfrac{1}{3}\)) (*)
\(\Leftrightarrow36x^2+16x+1=0\)
\(\Leftrightarrow x=\dfrac{-4\pm\sqrt{7}}{18}\)
Kết hợp (*) và ĐKXĐ ta được \(x=\dfrac{-4+\sqrt{7}}{18}\) là nghiệm phương trình